2020
DOI: 10.1186/s12302-020-00398-3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects in the fish embryo acute toxicity (FET) test: a catalogue of unspecific morphological changes versus more specific effects in zebrafish (Danio rerio) embryos

Abstract: Background The Fish Embryo Acute Toxicity (FET) test with the zebrafish (Danio rerio) embryo, the OECD test guideline (TG) 236, has been designed as an alternative for acute fish toxicity testing such as the OECD Acute Fish Toxicity Test (TG 203). To provide equivalent sensitivity to the acute fish test, the original FET test was designed to use only four morphological core endpoints: coagulation of the embryo, lack of somite formation, lack of heart beat, and non-detachment of the tail. These endpoints were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 95 publications
2
74
0
1
Order By: Relevance
“…In contrast, the concentration-response relationship of the insecticide carbaryl displayed a much steeper slope, i.e., sublethal and lethal toxicity data were much closer (EC 10 , 2.2 ± 0.26 mg/L, and LC 50 , 12.2 ± 0.72 mg/L). For further details and analyses of LC and EC data in zebrafish embryos, see von Hellfeld et al ( 2020 ), where FET observations were discussed in the context of a catalog of FET endpoints.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, the concentration-response relationship of the insecticide carbaryl displayed a much steeper slope, i.e., sublethal and lethal toxicity data were much closer (EC 10 , 2.2 ± 0.26 mg/L, and LC 50 , 12.2 ± 0.72 mg/L). For further details and analyses of LC and EC data in zebrafish embryos, see von Hellfeld et al ( 2020 ), where FET observations were discussed in the context of a catalog of FET endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to a previous communication, which aimed at compiling a comprehensive and standardized catalog of observations in the FET test (von Hellfeld et al 2020 ), the present study was designed to also analyze the onset and frequency (severity) of observations. Table 5 summarizes observations made at test concentrations ≤ EC 10 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example, drugs such as alcohol and nicotine that are known to affect human fetal development have been reported to induce morphological defects in the zebrafish embryos ( Lantz-McPeak et al, 2015 ). Spinal curvature can be further specified into three types: lordosis (spine curved inward), kyphosis (spine curved outward), and scoliosis (spine curved sideways) ( von Hellfeld et al, 2020 ). In this study, spinal curvature (scoliosis) was observed in mitragynine (50 μg/ml) and speciociliatine (25 and 50 μg/ml) exposed groups.…”
Section: Discussionmentioning
confidence: 99%